2013
DOI: 10.1111/ele.12081
|View full text |Cite
|
Sign up to set email alerts
|

The dimensionality of ecological networks

Abstract: How many dimensions (trait‐axes) are required to predict whether two species interact? This unanswered question originated with the idea of ecological niches, and yet bears relevance today for understanding what determines network structure. Here, we analyse a set of 200 ecological networks, including food webs, antagonistic and mutualistic networks, and find that the number of dimensions needed to completely explain all interactions is small ( < 10), with model selection favouring less than five. Using 18 hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
351
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 277 publications
(387 citation statements)
references
References 44 publications
17
351
2
1
Order By: Relevance
“…This suggests that our networks might be described using a reduced number of variables embedded in a low-dimensional space, as reported in previous work for food webs [16][17][18]22]. To substantiate this possibility we have quantified to what extent language networks are close to one-dimensional regular graphs by analysing their intervality.…”
Section: (Iv) Clusteringmentioning
confidence: 57%
“…This suggests that our networks might be described using a reduced number of variables embedded in a low-dimensional space, as reported in previous work for food webs [16][17][18]22]. To substantiate this possibility we have quantified to what extent language networks are close to one-dimensional regular graphs by analysing their intervality.…”
Section: (Iv) Clusteringmentioning
confidence: 57%
“…Examining the number of traits needed to predict species interactions in different ecological networks, Eklöf et al. (2013) analyzed studies using 6–21 traits and reported that little improvement was seen beyond three traits. In these studies, 11%–100% of network structure was predictable using even a single trait, although the identity of this key trait varied among networks.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with measuring many traits or investing time divining the best trait combinations, one might ask: “Why traits?” Although phylogenies can, in some cases, represent phenotypic and ecological differences among species (Flynn, Mirotchnick, Jain, Palmer, & Naeem, 2011; Gravel et al., 2012), phenotypic traits propose a mechanism. For example, traits determine whether and how two organisms might interact (Eklöf et al., 2013). Our study focuses attention on methodological decisions and sampling recommendations to propel this field forward.…”
Section: Discussionmentioning
confidence: 99%
“…Even for binary data, the inclusion of a few traits, such as the habitat use of the consumer or mobility of the resource, can substantially increase the proportion of correctly predicted food webs links (Eklöf et al, 2013). Trait-based approaches can thus complement expert knowledge and relatively sparse matrices of observational data in describing the structure of aquatic food webs; although I have focused on standing waters, the structure of model (1) can also be applied to marine food webs and running waters.…”
Section: Multi-trait Approaches and Functional Groups In Aquatic Foodmentioning
confidence: 99%
“…Even if we could define a single abstract feeding niche to characterize trophic links in a food web, body size may not correlate strongly with the niche parameters (Williams et al, 2010). Moreover, multidimensional niches requiring additional traits can describe the topology of empirical food webs with higher likelihood than one-dimensional niche models, including those based on body size (Alessina et al, 2008;Rohr et al, 2010;Williams and Purves, 2011;Eklöf et al, 2013). In less abstract terms, the presence and strengths of trophic links are affected by temperature (Henri et al, 2012;Rall et al, 2012), species identity (Nakazawa et al, 2011, Gilljam et al, 2011Rall et al, 2011), evolutionary history (Bersier and Kehrli, 2008), and predator and prey traits more mechanistically tied to the predation process (Winemiller, 1991;Wirtz, 2012;Klecka and Boukal, 2013).…”
Section: Introductionmentioning
confidence: 99%